Toxicological evaluation of alpha-galacto-oligosaccharides shows no adverse effects over a 90-day study in rats. (3rd July 2017) - Kruger, Claire; Beauchamp, Nicole; Modeste, Virginie; Morel-Despeisse, Fanny; Chappuis, Eric
AlphaGOS®, an alpha-galacto-oligosaccharides product, is a mixture of bi-, tri- and tetrasaccharides derived from oligosaccharides in the raffinose family of oligosaccharides (RFOs), naturally occurring plant-derived sugars. RFOs are alpha α-1, 6-linked chains of D-galactose attached to the 6-position of D-glucose and differ from the currently commercially available beta-galacto-oligosaccharides products in the chirality and glyosidic bonds. In order to determine the safety of AlphaGOS, rats were given 2000 mg AlphaGOS/kg/day daily via gavage over 90 days. Daily assessments of the animals showed no adverse clinical signs. No adverse treatment-related changes in feed consumption, body weight, clinical chemistry or hematology were noted. There were no adverse treatment-related changes in organ weights, gross or histopathology. Given these findings, it can be concluded that the no observed adverse effect level for AlphaGOS is greater than 2000 mg/kg/day.